[Pseudo-Craters at Lake Myvatn] - Streng, Evelyn Fiedler (1975)
Photograph of pseudo-craters at Lake Myvatn in Skútustaðir, Iceland. The large craters surround the light lake to the right, covered in green grass and black and grey rocks along its edges. Green fields sit along the feet of the structures. A road passes the main crater to the right alongside the lake. The silhouette of a mountain range is visible in the far distance to the right.